Impact of Mechanization on Productivity of Major Grain Crops in Punjab (Pakistan) (Journal of Asian Development Studies, 2023)
Farm mechanization is an essential element for food security in Pakistan. Farmers adopted new technology regarding agriculture to increase their farm productivity and to increase cultivable land. Due to farm mechanization, farm production increases and barren land is converted into cultivated land. This study aims to highlight mechanization's impact on the productivity of the farm, cultivation of the farms, and the status of mechanization. Primary data was collected from three different villages of district Khushab. The results showed an increase in cultivated land, which increased production. The yield of wheat and rice also increases due to mechanization